FACTORS INFLUENCING THE COMMUNICATION BEHAVIOR OF OIL PALM PLANTERS IN PELALAWAN DISTRICT - Aini Haryani; Roza Yulida; Yulia Andriani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
Communication behavior is an attitude or action that is in a person to obtain the information he needs. Communication behavior can describe how the smallholders' businesses obtain information about farming as a consideration in making decisions for their farming. Oil palm is a leading commodity in Riau Province, Pelalawan Regency is the area with the third largest area of oil palm plantations. The purpose of this study was to analyze the factors that influence the communication behavior of oil palm planters in obtaining information in the Pelalawan District. This research was conducted in Pangkalan Kuras District and Langgam District in Pelalawan Regency. The number of respondents in this study was 140 people who were obtained using the purposive sampling method. The data that has been obtained are then analyzed using Structural Equation Modeling (SEM). The results showed that five factors influenced the planters' communication behavior. Internal characteristics had a negative influence on the farmer's communication behavior, external characteristics, and information sources had a positive influence, while the communication media and program communications had a positive and significant influence on the planters' communication behavior.